Promosi Kesehatan Dengan Media Booklet Dan Media Leaflet Dalam Meningkatkan Pengetahuan Ibu Hamil Tentang ASI Ekslusif: Health Promotion Using Booklet and Leaflet Media in Improving Knowledge of Pregnant Women About Exclusive Breastfeeding - Sri Maryati; Damai Yanti (LPPM STIKES Guna Bangsa, 2024)
Good nutrition is a very important factor in the first two years of a child's life because it can reduce the risk of chronic disease, reduce morbidity, and can encourage better overall development, one of which is breastfeeding. Breastfeeding can also prevent the death of more than 820,000 children under the age of five every year. The purpose of this study was to determine differences in the knowledge of pregnant women about exclusive breastfeeding in the group that was given booklets and leaflets as the control group. This research is a pre-experimental study with a posttest only control group design. The population in this study were pregnant women in the working area of the Batujajar Health Center with a total of 497 pregnant women. The sample in this study were 30 pregnant women. The analysis in this study used an unpaired t test. The results showed that there was no difference in the knowledge of pregnant women about exclusive breastfeeding in the group that was given booklets and leaflets with p = 0.566 > 0.05. It is recommended for public health centre B to use booklets and leaflets as media for health promotion in according to conditions and needs of the local community